Operando Study of Thermal Oxidation of Monolayer MoS(2) - Park, Sangwook (John Wiley and Sons Inc., 2021)

(untitled) (Adv Sci (Weinh))
Monolayer MoS(2) is a promising semiconductor to overcome the physical dimension limits of microelectronic devices. Understanding the thermochemical stability of MoS(2) is essential since these devices generate heat and are susceptible to oxidative environments. Herein, the promoting effect of molybdenum oxides (MoO(x)) particles on the thermal oxidation of MoS(2) monolayers is shown by employing operando X‐ray absorption spectroscopy, ex situ scanning electron microscopy and X‐ray photoelectron spectroscopy. The study demonstrates that chemical vapor deposition‐grown MoS(2) monolayers contain intrinsic MoO(x) and are quickly oxidized at 100 °C (3 vol% O(2)/He), in contrast to previously reported oxidation thresholds (e.g., 250 °C, t ≤ 1 h in the air). Otherwise, removing MoO(x) increases the thermal oxidation onset temperature of monolayer MoS(2) to 300 °C. These results indicate that MoO(x) promote oxidation. An oxide‐free lattice is critical to the long‐term stability of monolayer MoS(2) in state‐of‐the‐art 2D electronic, optical, and catalytic applications.